NILAI-NILAI MORAL DALAM FILM NGERI-NGERI SEDAP KARYA BENE DION (KAJIAN STRUKTURAL) - Sri Wahyuni; Abdoel Gafar; Sainil Amral (Universitas Batanghari, 2024)
This research was motivated by finding moral values in the film Ngeri-ngeri-Sedap by Bene Dion. This research aims to describe the moral values in the film Ngeri-ngeri Sedap by Bene Dion. This research uses a qualitative descriptive method. Quotation data was analyzed based on theory and was used as a theoretical basis for analyzing this research. This type of descriptive, qualitative research is used as a way to describe the moral values contained in the film Ngeri-ngeri Sedap by Bene Dion. The results of this research can be described that the film Ngeri-ngeri Sedap by Bene Dion contains the moral values of the aspects of caring for others, helping each other, deliberating, forgiving and respecting others. The number of findings used as data in the form of quotes about moral values was 72 quotes. From the results of this research, it can be seen that the film Ngeri-ngeri Sedap by Bene Dion contains moral values that can be used as viewing material for the public and as material for moral education in schools.